THU0555 Validation of a Portable Device (RE.MO.TE.) for the Hand Functional Assessment in Patients with Chronic Rheumatic Diseases. (23rd January 2014) - Piga, M.; Tradori, I.; Pani, D.; Cauli, A.; Dessì, A.; Garau, P.; Porru, G.; Barabino, G.; Vacca, A.; Raffo, L.; Mathieu, A.
Abstract : Background: Patients with inflammatory rheumatic diseases characterized by a chronic progressive course, such as Rheumatoid Arthritis (RA) and Systemic Sclerosis (SSc), develop a disability of the hand which requires an adequate assessment and therapeutic intervention through a pharmacological treatment and a proper rehabilitation program. The Re.Mo.Te. device consists of sensorized aids, allowing the execution of hand rehabilitation exercises and the extraction of relevant parameters (motion, force, pressure, speed of execution) from the analysis of several repetitions of the same movement, performed in real rehabilitation exercises typically prescribed to RA and SSs patients (1 ). These data are part of a larger project called Re.Mo.Te. Recovery Movement and Telemonitoring for rheumatology patients with disabilities of the hand. Objectives: To validate portable device Re.Mo.Te for the evaluation of hand disability in patients with RA and SSc. Methods: Ten RA patients (10F, age 56.9 ± 13.1 years) and 10 SSc patients (9F, age 56.3 ± 10.4 years) underwent an assessment of hands function through the device Re.Mo.Te. and through the measurement of: 1) Range Of Movement (ROM) of the wrists and 2) grip strength (pinch and grip) of the hand and fingers, 3) hands and fingers extension. The HAQ and the algo-functional index of Dreiser were administered to both RA and SSc patients while the Hamis test was administered exclusively to SSc patients. The Spearman's correlation coefficient was applied to test the validity of the results obtained with the Re.Mo.Te. device and to compare them with traditional assessment; p values ​​<0.05 were considered significant. Results: All patients had a reversible hand disability (HAQ = AR: 1.5 ± 0.82; SSc: 1.4 ± 0.65 - Dreiser's index = AR: 15.7 ± 6.0; SSc: 15.0 ± 5.7). The Spearman's correlation coefficients between the traditional hand functional assessment and the Re.Mo.Te. device assessment were high (0.67-0.79) and statistically significant for the measurement of grip strength (p <0.0001) and overall extent (p <0.001). The ROM results showed significant correlation with the global finger extension (p <0.01) and the speed of fingers extension (p <0.001) abilities evaluated by Re.Mo.Te. Conclusions: The Re.Mo.Te. device is a valuable aid for the assessment of hand disability in chronically ill subjects requiring a quantitative evaluation for the proper set up of a personalized rehabilitation program. References: D. Pani, G. Barabino, A. Dessì, M. Piga, I. Tradori, A. Mathieu, L. Raffo "An integrated Portable Device for the hand functional assessment in the clinical practice" Biomedical Engineering Systems and Technologies 2012 - Revised Selected Papers, J. Gabriel et al. Eds., in press Disclosure of Interest: None Declared